Commercial and Pre-Commercial Cell Detection Technologies for Defence against Bioterror : Technology, Market and Society. - Lechuga, L. M. (NATO Science for Peace and Security Series: Human and Societal Dynamics, v. 39., 2008)
As a response to the rapidly emerging threat of bioterrorism, this volume aims to exchange information on commercially available technologies and equipment for defense against bioterrorism; to further the development of new biosensor system prototypes into a commercially available apparatus and to explore human factors in BWA biosensors.